2017
DOI: 10.1016/j.palaeo.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A new correlation of Triassic–Jurassic boundary successions in NW Europe, Nevada and Peru, and the Central Atlantic Magmatic Province: A time-line for the end-Triassic mass extinction

Abstract: Understanding the end-Triassic mass extinction event (201.36 Ma) requires a clear insight into the stratigraphy of boundary sections, which allows for long-distance correlations and correct distinction of the sequence of events. However, even after the ratification of a Global Stratotype Section and Point, global correlations of TJB successions are hampered by the fact that many of the traditionally used fossil groups were severely affected by the crisis. Here, a new correlation of key TJB successions in Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 81 publications
4
107
0
1
Order By: Relevance
“…Such short and powerful eruptions may have had a severe impact on global climate by limiting the time in which negative feedback processes, such as the weathering of Ca-Mg silicates, can abate warming and acidification. CAMP magmatism coincided in time with three marked negative carbon isotope excursions bracketing the main extinction period 20,24,25 , and with an inferred strong rise of atmospheric CO 2 8,9 . In general, the pulsed magmatic and degassing activities of LIPs 6,7 can cause a rapid rise of atmospheric CO 2 and greenhouse conditions, which are reflected by rapid δ 13 C negative excursions recorded in both organic matter and carbonates 10 , testifying to a global perturbation of the exogenic (i.e., superficial) carbon cycle.…”
mentioning
confidence: 83%
“…Such short and powerful eruptions may have had a severe impact on global climate by limiting the time in which negative feedback processes, such as the weathering of Ca-Mg silicates, can abate warming and acidification. CAMP magmatism coincided in time with three marked negative carbon isotope excursions bracketing the main extinction period 20,24,25 , and with an inferred strong rise of atmospheric CO 2 8,9 . In general, the pulsed magmatic and degassing activities of LIPs 6,7 can cause a rapid rise of atmospheric CO 2 and greenhouse conditions, which are reflected by rapid δ 13 C negative excursions recorded in both organic matter and carbonates 10 , testifying to a global perturbation of the exogenic (i.e., superficial) carbon cycle.…”
mentioning
confidence: 83%
“…The stratigraphic framework for discussing the PGE data is based on Lindström et al 44 and is shown in Fig. 2.…”
Section: Stratigraphic Framework and Carbon Isotope Anomalies Of Etementioning
confidence: 99%
“…Warrington, 1983;Mettraux and Mohr, 1989;Embry and Suneby, 1994;Warrington et al, 1995;Kürschner et al, 2007;Bonis et al, 2009;Ruckwied and Götz, 2009) and papers on sequence stratigraphy (e.g. Paterson et al, 2016;Lindström et al, 2017b) Table 1). The composition of these Late Triassic assemblages varies, and is often poorly known in part due to a lack of quantitative data.…”
Section: Triassic Dinoflagellate Cysts State-of-the-artmentioning
confidence: 99%
“…Lindström 2002 Lindström (2006); these two forms may reflect different salinity levels. Only one occurrence of Lunnomidinium scaniense from Schandelach, Germany has been reported outside Sweden (Lindström et al, 2017b). Lindström and Erlström (2006b) Several studies recorded Rhaetian dinoflagellate cysts from south-eastern France (Doubinger and Adloff, 1977;Adloff and Doubinger, 1982;Fauconnier et al, 1996;Courtinat et al, 1998;2002;Courtinat and Piriou, 2002).…”
Section: Europementioning
confidence: 99%